Numerical Simulation of the Hot Isostatic Pressing Densification Behavior of Ti6Al4V Powder for a Thin-Walled Tubular Component with Non-Axisymmetric Inner Ribs - Yanqing Jiang; Lin Geng; Guofeng Zhang (Metals)
Hot isostatic pressing (HIP) technology is an efficient near-net-shape forming method to prepare complex-shaped structural components. However, for non-axisymmetric components with a complex shape, the powder flow and densification behaviors during HIP are still not clear, leading to a need for lots of experiments to optimize the process parameters. In the current work, a typical aerospace thin-walled tubular component with non-axisymmetric inner ribs was selected as the research object, and its instantaneous powder flow and relative density during the whole HIP process were investigated by a numerical simulation method, focusing on the influence of HIP process conditions on powder densification. The simulation results indicate that the upper end of the Ti6Al4V thin-walled tubular part is preferentially densified, and the lowest densification is observed at the inner rib of the cylinder wall. Moreover, the effect on densification of each HIP condition, including sintering temperature (900–970 °C), pressure (120–180 MPa), and holding time (3–4 h), was evaluated separately. The HIP sintering temperature contributes the most to the improvement of densification, followed by the pressure, while the holding time contributes the least. Investigating HIP densification behavior is beneficial to the structural and process optimization of metal near-net-shape forming applications.